On a New Subclass of p-Valent Close-to-Convex Mappings Defined by Two-Sided Inequality. (28th June 2018) - Xu, Yi-Hui; Liu, Jin-Lin
Abstract : A new subclassK p ( α 1, α 2, β ) ofp -valent close-to-convex mappings defined by two-sided inequality is introduced. Some sufficient conditions for functions to be inK p ( α 1, α 2, β ) are given.